New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon - Schnabel, Kareen E.; Bruce, Niel L. (Zootaxa, 2006)
Three species of the genus Munidopsis are currently known from New Zealand waters: M. marginata (Henderson, 1885), M. kaiyoae Baba, 1974 and M. abyssicola Baba, 2005. New records for M. marginata and M. kaiyoae around New Zealand are provided and Munidopsis maunga n. sp. and M. papanui n. sp. are described from a seamount on the Kermadec volcanic arc and the Papanui canyon off the southeast coast of New Zealand, respectively.